Geochemistry and provenance of core sediments from the southwestern Okinawa Trough - Huang Kuo-Ming; Lee Yung-Tan; Chang I-An; Huang Ren-Yi; Lin Meng-Lung; Hu Yen-Tsui (Oceanological and Hydrobiological Studies)
Understanding the sedimentary processes and provenance in the Okinawa Trough is critical for reconstructing regional tectonic evolution and sediment transport dynamics in this active back-arc basin. This study focuses on the geochemical characteristics of cored sediments from the southwestern Okinawa Trough to investigate their depositional processes and sediment source contributions. Geochemical analysis, including major and trace element concentrations as well as rare earth element (REE) patterns, reveals that REEs are predominantly associated with clay minerals, indicating their key role in sediment transport and diagenesis. La–Th–Sc ternary plots suggest a mixed provenance, with sediment contributions from northeastern Taiwan, the East China Sea continental shelf, and volcanic material from the Okinawa Trough. A three-end-member mixing model was applied to estimate the relative contributions of these sources. Results indicate that sediments from the Lan-Yang area in northeastern Taiwan account for approximately 54.63% of the total input, followed by 24.12% from the East China Sea shelf and 21.25% from local volcanic sources. The spatial distribution of source contributions further reflects the influence of fluvial input and ocean currents on sediment dispersal. These findings offer new insights into sedimentary processes and tectonic activity in the region.